Intellectual leadership in higher education : renewing the role of the university professor - Macfarlane, Bruce, 1961- (New York : Routledge, 2012)
'There is growing research and literature about Intellectual Leadership and management in higher education. However, there has been little consideration of the formal and informal leadership role of full professors. This group of individuals are key to the leadership of universities and they represent a group of individuals at the apex of their discipline or profession with considerable expertise across many elements of academic practice including research, teaching and service activities incorporating leadership and management roles. In this context, the role of professors as'intellectual leaders' is under-theorised and higher education institutions make insufficient use of professors as an internal resource. This book tackles the question of what intellectual leadership actually is and analyses other question marks associated with the role of senior academics Intellectual Leadership in Higher Education provides a theoretical exploration of the meaning of intellectual leadership with particular reference to university professors and other senior academics. It draws on new international research data involving several hundred university professors in Europe, North America, Asia and Africa and also provides a series of practical ideas and recommendations for defining the role of a university professor more clearly. This careful analysis of academic roles will prove invaluable for all those working in Higher Education'-- Provided by publisher.
Keywords: College teachers -- Professional relationships; Educational leadership